MEDIASTINITIS, WHAT SHOULD WE KNOW: A CASE REPORT OF PNEUMOPYOTHORAX WITH SUSPECTED MEDIASTINITIS IN A 67-YEAR-OLD MALE - Aditya, Aldo; Erawati, Dini Rachma (International Journal of Radiology and Imaging, 2024)
Mediastinal disease consists of various diagnoses that have different characteristics, and the severity is not the same. The mediastinal disease diagnosis is often delayed because of the non-specific and sometimes vague presentation and clinical symptoms. One of the commonly missed diagnoses is acute mediastinitis, which is usually presented with fever, pleuritic or retrosternal chest pain, and an inflammatory syndrome. Careful clinical evaluation and radiological correlation are essential when diagnosing mediastinitis, as well as the need to differentiate it from mediastinal infiltration due to malignancy. In this case report, we describe a 67-year-old male, who was referred with pyothorax, cough, and 10 kg of weight loss in the last 1 month. The patient then underwent a CT examination with contrast to establish the diagnosis. Finally, the patient was diagnosed with pneumopyothorax with suspicion of mediastinitis and abscess formation. The lessons learned from this case include the need for recognizing features of mediastinitis, such as fat stranding and fluid collection, which may contain gas locules, in the mediastinal region. The aim of this case report is to increase awareness of early signs of mediastinitis so that prompt management can be initiated as early as possible. Keywords: Mediastinitis, pneumopyothorax, CT thorax